Grenada. Significant Achievements 2019 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The main activities carried out by the Institute in Granada during 2019 are identified, with respect to the needs and interests of the country, strengthening the food security and safety systems, occupational health, the link between agriculture and the tourism industry and the sustainable use of local foods. Likewise, it contributed to the improvement of the management of the coconut cultivation fields.